Cloning and characterization of a new laccase from Bacillus licheniformis catalyzing dimerization of phenolic acids - Koschorreck, Katja; Richter, Sven M; Ene, Augusta B; Roduner, Emil; Schmid, Rolf D; Urlacher, Vlada B (Applied microbiology and biotechnology, 2008)
A new laccase gene (cotA) was cloned from Bacillus licheniformis and expressed in Escherichia coli. The recombinant protein CotA was purified and showed spectroscopic properties, typical for blue multi-copper oxidases. The enzyme has a molecular weight of ~65 kDa and demonstrates activity towards canonical laccase substrates 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS), syringaldazine (SGZ) and 2,6-dimethoxyphenol (2,6-DMP). Kinetic constants K M and k cat for ABTS were of 6.5 ± 0.2 μM and 83 s⁻¹, for SGZ of 4.3 ± 0.2 μM and 100 s⁻¹, and for 2,6-DMP of 56.7 ± 1.0 μM and 28 s⁻¹. Highest oxidizing activity towards ABTS was obtained at 85°C. However, after 1 h incubation of CotA at 70°C and 80°C, a residual activity of 43% and 8%, respectively, was measured. Furthermore, oxidation of several phenolic acids and one non-phenolic acid by CotA was investigated. CotA failed to oxidize coumaric acid, cinnamic acid, and vanillic acid, while syringic acid was oxidized to 2,6-dimethoxy-1,4-benzoquinone. Additionally, dimerization of sinapic acid, caffeic acid, and ferulic acid by CotA was observed, and highest activity of CotA was found towards sinapic acid.